ПРОГНОЗ ДАТЫ НАСТУПЛЕНИЯ ФЕНОЛОГИЧЕСКОЙ ФАЗЫ КУЩЕНИЯ - Ермакова (Ermakova Lyudmila) Людмила Николаевна; Толмачева (Tolmacheva Natalia) Наталья Игоревна (Географический вестник=Geographical bulletin, 2017)
Дается схема прогноза дат наступления определенных периодов в развитии растений. Учитываются особенности атмосферной циркуляции. Разработана синоптико-статистическкая схема прогноза даты наступления фенологической фазы кущения. The date’s prognosis of the beginning of the periodical derivation phase In the article, stage-by-stage scheme, the dates forecast of approach, of a phenological phase vegetation for separate points of the Perm edge is given. The advance time of the forecast makes from 1,5 months till 2 weeks. At each subsequent stage, probably, specification of the forecast. Increase of accuracy of the forecast is promoted by inclusion in the equations of regress of such indicators, as corners of an inclination of axes high-rise synoptic crests and hollows to latitude to circles, a difference of geopotentials Н500, basically, synoptic formations. The indicator heat capacity is significant only for a southern part of territory of the Perm edge. In quality prediction parametres of atmospheric circulation from informative territories are used. The estimation of the equations: on dependent materials and independent materials, that allows considering results of the forecast as a successful once.